The Balkan and Baltic experience of financial services privatization - John Consigilio (The European Association for Banking and Financial History (EABH), 2014)
The financial services sectors of Romania and Estonia moved towards privatization in sharply contrasting manners. For a long time Romania's enthusiasm for its 1998 promise to the IMF to privatize its leading banks was only a commitment on paper; few steps were made towards its fulfillment. By contrast, Estonia's experience of privatization was generally a positive one, based on norms and structures often comparable to those in advanced industrial economies.
Keywords: G21; G28; N24; P34; 330; privatization; financial; services; Romania; Estonia; EBRD; IMF